A solution to the optimal long-range hydrothermal dispatch problem using the first-order gradient method - Uy, Domingo Luy (1979)
The optimal long range hydrothermal dispatch problem with fixed final state is considered. A simplified model of a hydrothermal system with the effects of state and control inequality constraints included, is employed. The penalty function method in conjunction with the First-Order Gradient technique has been applied to determine the optional water usage policy of a system of 2 reservoir-type and 3 regulating pondage-type hydroplants with one equivalent thermal plant.